Assessment on 3D reconstruction of vehicle damage by using close range photogrammetry / Nurul Shafiqah Hazelin Noor Azmin - Noor Azmin, Nurul Shafiqah Hazelin (2018)
Total of road accident rose surprisingly during festive season. In addition, road accidents may lead in injury, death or property damage. The relevant of the study may assist in determining the percentage of the car damage for cost estimation. At the end of study, based on the outcome, it can provide the solving and methodology to analyze vehicle damage and achieving the cost estimation of vehicle deformation. This study examined the percentage of vehicle damage from front side. The percentage obtained used for cost estimation. A simple surveyed done to workshop to be know the real price based on the damaged, and then compared the cost. The aim of this study is to analyse vehicle damage to gain the percentage of damage for getting with the real cost. Data used in this study obtained by using close range photogrammetry method. A vehicle image captured, and then processed into Photomodeler. Percentage computation done by referring the amount of volume of damage before and after the vehicle accident. Last for estimating cost by comparing to the real price at workshop. In conclusion, the expected result shows 3D image of rear vehicle component, percentage of damages and cost. As for contribution this study helps the car owner when having an accident or insurance companies evaluating the material damages caused by a traffic accident, includes the accurate knowledge of the vehicle body deformations and the degree of car damages. Besides, it helps in cost estimation for car damage to get repaired.